Exegesis Integrative Review of Salvation Because The Love Of God Is The Basic of The Church As The Unity of The Body of Christ (Ephesians 2:11-22) - Tonny Andrian (Jurnal Didaskalia, 2020)
The subject of the unity of the church has appeared several times during the period of church history as a major subject. Even in the 20th century, differences of opinion on the subject of unity led to divisions. This point cannot be ignored. That is why the researcher conducted an integrated exegessa study on the meaning of the Church as the unity of the body of Christ Ephesians 2: 11-22. Ephesians 2: 11-22 is not a separate passage, but integrative, with other passages in the book of Ephesians. (this would be integrative both with Ephesians 2: 1-10 and Ephesians 4: 1-6) The conjunction "therefore" in Ephesians 2.11, describes the preceding verses that speak of grace. The suffering of Jesus Christ and His sacrifice on the cross, and His shed blood, are manifestations of grace that saves sinners. A demonstration of grace, which is free gift. It is the grace that saves people from sin. Thus Ephesians 2: 11-22 must be seen as a context that comes from grace. The saving or salvation based on the grace of God, as a building body of Christ, which is a union, which was previously "distant", ie those who are without Christ, not belonging to the citizens of Israel, become one body of Christ as intended by God. Ephesians 2: 11-22 explains that the unification of the body of Christ is a reflection of the journey of a Christian individual who has been saved by the grace of Christ God, is united or united with other Christian individuals to move towards the unity of building the body of Christ, as the Temple of God. the church as the unified Body of Christ, is built on the teachings of the Apostles and Prophets. Thus, the church, which has a government, a doctrine that may not be the same as one another, but the church is a unity in the bonds of the Spirit of peace, one faith, one Baptism, one god, one GOD the FATHER of all God, as salt and The light of the world, brings transformation and restoration for the world, through the carrying out of the task of the grace of Christ, namely the preaching of the gospel of the kingdom of heaven, so that all knees will kneel and all tongues confess that Jesus Christ is Lord to the glory of the heavenly Father.